Sensoriamento quasi-distribuído de forças com transdutores de redes de Bragg em fibras óticas - Pedroso, Marcelo Antonio (2018)
This work describes the development of a tactile sensing array instrumented with fiber Bragg gratings. The system can detect up to four loads simultaneously applied on the array in different positions by using compressive sensing. The sensing array is composed of six Bragg gratings encapsulated in a sheet of silicone elastomer with the aid of a mold manufactured with a 3D printer. Response and sensitivity to applied loads and temperature changes, were assessed for one encapsulated FBG. Results obtained in tests of force mapping with the sensor array divided into eight sensing areas are presented. Average SNR higher than 19 dB and relative mean errors less than 10.5 % were obtained. The ability of the sensor array to detect forces applied by the finger tips is also demonstrated.